2012
DOI: 10.1172/jci64026
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy as a mechanism for stress-induced liver adaptation

Abstract: Over half of the mature hepatocytes in mice and humans are aneuploid and yet retain full ability to undergo mitosis. This observation has raised the question of whether this unusual somatic genetic variation evolved as an adaptive mechanism in response to hepatic injury. According to this model, hepatotoxic insults select for hepatocytes with specific numerical chromosome abnormalities, rendering them differentially resistant to injury. To test this hypothesis, we utilized a strain of mice heterozygous for a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(180 citation statements)
references
References 38 publications
7
171
0
2
Order By: Relevance
“…fumaryl-acetoacetate hydrolase (FahA), the enzyme that detoxifies the disease-causing IC, shows that selection favors liver cells that lack homogentisate dioxygenase (Hmg1), which is responsible for the production of the IC in the first place (41). Intriguingly, whereas the two genes form a divergently oriented DNGP in several fungi (Fig.…”
Section: Phytophthora Infestansmentioning
confidence: 99%
“…fumaryl-acetoacetate hydrolase (FahA), the enzyme that detoxifies the disease-causing IC, shows that selection favors liver cells that lack homogentisate dioxygenase (Hmg1), which is responsible for the production of the IC in the first place (41). Intriguingly, whereas the two genes form a divergently oriented DNGP in several fungi (Fig.…”
Section: Phytophthora Infestansmentioning
confidence: 99%
“…During postnatal development, a scheduled division program characterized by incomplete cytokinesis results in the genesis of binuclear tetraploid hepatocytes (2x2n), which subsequently play a pivotal role in liver polyploidization (3,(9)(10)(11). Remarkably, during postnatal development and adult life, hepatocytes are able to increase their DNA content but also reduce it through a process call "ploidy reversal" (2,12). In fact, polyploid hepatocytes undergo multipolar mitosis, producing daughter cells with half the chromosome content but also with aneuploid content.…”
Section: Introductionmentioning
confidence: 99%
“…Duncan et al (13) suggested that polyploid hepatocytes underwent aberrant mitoses with high levels of chromosome mis-segregation, thereby generating aneuploidy among polyploid cells. The authors further speculated that aneuploidy endows hepatocytes with phenotypic variability and adaptability upon exposure to various noxious agents and metabolic stresses (15).…”
mentioning
confidence: 99%